2003
DOI: 10.1177/095440700321700903
|View full text |Cite
|
Sign up to set email alerts
|

A driving cycle for electrically-driven vehicles in Rome

Abstract: In the research results presented here, an average driving cycle is synthesized for an electrically driven car moving in the city of Rome. The technique of Lyons et al. [1] for synthesizing a statistically representative driving cycle was used on a 5 week acquisition set of data collected with a duly equipped electric Citroen Saxo that was driven for over 3100 km by six di erent drivers in the months of May and June 2001 in Rome. The driving cycle developed is compared with the other available cycles, especial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…It must be questioned whether the ADR 81/02 urban test profile typifies urban Australian driving. The development of the much more realistic WLTP is a clear indication that the NEDC testing does not approximate actual driving in the EU, and real [20, 49, 50]. The drive test route used in this research had fewer periods of acceleration, higher levels of acceleration, longer periods of constant speed and a higher average speed than the NEDC/ADR profile, and could be argued to be closer to the drive cycle used in the WLTP.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…It must be questioned whether the ADR 81/02 urban test profile typifies urban Australian driving. The development of the much more realistic WLTP is a clear indication that the NEDC testing does not approximate actual driving in the EU, and real [20, 49, 50]. The drive test route used in this research had fewer periods of acceleration, higher levels of acceleration, longer periods of constant speed and a higher average speed than the NEDC/ADR profile, and could be argued to be closer to the drive cycle used in the WLTP.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Mean absolute acceleration for the MOVES DS ranges from 0.1 to 0.6 m/s 2 , and for the OR-217 DS from 0.2 to 0.4 m/s 2 . Beyond the unique mechanical performance of advanced vehicles, some studies have suggested that new engine/power train technologies could influence driving patterns (Alessandrini and Orecchini 2003;US Environmental Protection Agency 2006). Given the uncertainty that this is a real effect -and if it is real, what exactly the effect would be -the same DSs are used for all vehicles modeled in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Drive cycles can be developed by three major approaches, namely, the extrapolation method, selection method and simulation method [4]. The extrapolation method is used to build modal drive cycles.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The amount of these emissions gives the most effective understanding of the air quality impact of on-road traffic. Two different approaches are widely used to calculate vehicle emissions: emission testing and emission modeling [4,5]. Vehicle emission testing is a process in which vehicles are running through a movement pattern while equipped with emission-measuring instrument, such as the portable emission measurement system (PEMS) [6].…”
Section: Introductionmentioning
confidence: 99%